1997
DOI: 10.1152/ajpendo.1997.273.5.e903
|View full text |Cite
|
Sign up to set email alerts
|

Role of the kidney in human leptin metabolism

Abstract: To assess the role of the human kidney in leptin metabolism, we measured renal leptin net balance and urinary leptin excretion in 16 normal postabsorptive volunteers with varying degrees of obesity. Arterial leptin concentrations (11.6 ± 2.7 ng/ml) significantly exceeded renal vein concentrations (10.3 ± 2.5 ng/ml, P < 0.001). Renal leptin fractional extraction averaged 13.1 ± 1.1%, and renal leptin net balance (uptake) averaged 1,070 ± 253 ng/min. Lineweaver-Burk analysis indicated that renal leptin uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
4

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 14 publications
3
61
1
4
Order By: Relevance
“…Meyer et al reported an inverse relationship between renal fraction leptin extraction and circulating leptin level, and have suggested that renal uptake is a saturable process modelled by Michaelis ± Menton kinetics. 33 It is dif®cult to reconcile these ®ndings with our results which demonstrate that plasma clearance is virtually the same in monkeys as the value reported in humans, when plasma leptin levels in the monkeys were 1 ± 2 orders of magnitude higher.…”
Section: Discussionmentioning
confidence: 38%
“…Meyer et al reported an inverse relationship between renal fraction leptin extraction and circulating leptin level, and have suggested that renal uptake is a saturable process modelled by Michaelis ± Menton kinetics. 33 It is dif®cult to reconcile these ®ndings with our results which demonstrate that plasma clearance is virtually the same in monkeys as the value reported in humans, when plasma leptin levels in the monkeys were 1 ± 2 orders of magnitude higher.…”
Section: Discussionmentioning
confidence: 38%
“…37 Finally, since the calculated apparent K m of $ 10 ngaml for renal leptin uptake is close to physiological plasma leptin levels, small alterations of plasma leptin concentrations may result in major changes of leptin elimination. 38 Thus, increased renal leptin elimination by glomerular ®ltration andaor tubular metabolism might contribute to the observed decrease of plasma leptin concentrations in our diabetic patients who did not suffer from renal insuf®ciency.…”
Section: Discussionmentioning
confidence: 73%
“…Estimates and 95% confidence intervals for additive genetic (h 2 , heritability) and common (c 2 ) and specific (e 2 ) environmental influences on the various phenotypes were obtained by univariate modelling of variance-covariance matrices in female monozygotic (MZ) and dizygotic (DZ) twin pairs 14 using Mx software. 11 Results are presented for the best-fitting and most parsimonious models based on the residual w 2 . In addition, heritabilities were tested against zero using a Wilcoxon two-group test of the effect of zygosity on absolute within-pair phenotypic differences.…”
Section: Methodsmentioning
confidence: 99%
“…This result implies that as fat mass increases leptin secretion increase disproportionately. 8,11,16 However, when gender was included in the model, the resulting estimate of the exponent relating ln(leptin) and ln(fat mass) was no longer different from 1 (1.10 AE 0.06, Table 2, model Ic). This represents the average relationship in males and females, and suggests that the gender effect, whatever its mechanisms, acts to vary leptin secretion either side of close proportionality with total fat mass.…”
Section: Determinants Of Circulating Leptinmentioning
confidence: 98%
See 1 more Smart Citation